2020
DOI: 10.1039/c9ta14174j
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-enhanced electrocatalytic oxygen reduction in alkaline media on gold nanohole electrodes

Abstract: Plasmon-driven chemical transformation has become a promising approach for enhancing sluggish electrocatalytic reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…First, a gold nanoholes array with holes of an average diameter of 630 nm and center-to-center spacing of 980 nm was constructed using colloidal nanolithography, as shown in recent articles. 13,20 The gold thin film was deposited on top of an ultrathin (<5 nm) Ti/TiO 2 adhesion layer, as mechanistic investigations revealed that Ti/TiO 2 /AuNHs-based plasmonic electrodes are an efficient source of hot electrons, contributing to their injection into the underlying TiO 2 -based adhesion layer and improving the electrochemical reduction of water. 13 Indeed, such electrodes support the LSPR modes (Figure 1b) at 660 nm with a broad maximum at around 980 nm with an increase in absorption at <500 nm due to the underlying Kapton substrate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…First, a gold nanoholes array with holes of an average diameter of 630 nm and center-to-center spacing of 980 nm was constructed using colloidal nanolithography, as shown in recent articles. 13,20 The gold thin film was deposited on top of an ultrathin (<5 nm) Ti/TiO 2 adhesion layer, as mechanistic investigations revealed that Ti/TiO 2 /AuNHs-based plasmonic electrodes are an efficient source of hot electrons, contributing to their injection into the underlying TiO 2 -based adhesion layer and improving the electrochemical reduction of water. 13 Indeed, such electrodes support the LSPR modes (Figure 1b) at 660 nm with a broad maximum at around 980 nm with an increase in absorption at <500 nm due to the underlying Kapton substrate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To achieve ultra broadband absorption of light multi radii InAs NW based structure is proposed and is found to be the most efficient as it exhibits high short circuit current density and perfect light absorption for a broad range of wavelength which covers significant portion of the solar spectrum. Polarization and angle sensitivity of the optimized structure is also investigated and the results signify the potential of the proposed structure as the absorber layer of thin-film photonic devices and such absorption characteristics can have profound impact in the field of photochemistry 48 and photoelectrochemistry 49 as well. The analysis and discussions would also give an intuitive perception behind the ultra broadband absorption characteristics of the optimized structure.…”
Section: Introductionmentioning
confidence: 90%
“…Regarding the additional energy sources, it is noteworthy that plasmonic metal nanocrystals (NCs) have shown great potential for solar-to-chemical energy conversion due to their strong interaction with light through the excitation of a localized surface plasmon resonance (LSPR). In fact, the incorporation of plasmonic metal NCs into conventional catalysts could lead to an improvement in the catalytic activity for the hydrogen evolution reaction, , oxygen evolution reaction, MOR, and ORR upon visible-light irradiation. This can be attributed to the promotional effects of hot carriers generated by the LSPR excitation of plasmonic metal NCs upon irradiation.…”
mentioning
confidence: 99%